SPECTROPHOTOMETRIC METHODS FOR THE QUANTIFICATION OF CARISOPRODOL USING FERRIC CHLORIDE, O-PHENANTHROLINE, AND P-NITROANILINE, SODIUM NITRITE AS ANALYTICAL REAGENTS - D, MURALI; RAO G, PURNA CHANDRA (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The present study represents the development of two spectrophotometric methods for the determination of carisoprodol (CCP) in pure and formulations using ferric chloride, o-phenanthroline, and p-nitroaniline (PNA), sodium nitrate as analytical reagents. Methods: The proposed spectrophotometric methods were developed based on oxidation of Fe3+ by CCP, and then, the resultant product was reacted with o-phenanthroline in acidic condition forms an orange-colored complex and diazotization of PNA followed by coupling with CCP in an alkaline medium forms yellow-colored complex. Results: Under the optimized conditions, the absorbance of CCP concentration obeyed the Beer’s law in the ranges of 10–60 μg/mL with good correlation coefficient values of 0.9992 and 0.9990 with the limit of detection values of 1.286 and 2.408 μg/mL, respectively. Conclusion: The proposed methods were successfully applied for the determination of CCP in pure and in their formulations.